Paid Parking Performance Evaluation at Depok Baru Station - Syaiful, Syaiful; Murtejo, Tedy; Rulhendri, Rulhendri; Gunawan, Dede; Wardhani, Asri Kusuma; Lestari, Dini Hari Mulya (Universitas Ibn Khaldun Bogor, 2025)
Depok Baru Station is a train operating facility that stops regularly to pick up and drop off passengers, Depok Baru Station is in the operational area of DAOP 1 Jakarta. Depok Baru Station has so many passengers that one of the motorized vehicle parking facilities cannot accommodate vehicles parked in the area at Depok Baru Station. Therefore, it is necessary to study parking analysis at Depok Baru Station to provide benefits for motorbike users who do not get parking space, this is to create comfort and security for passengers who park their motorbikes in the Depok Baru Station area. So that it can provide an alternative parking control at Depok Baru Station so that no more motorized vehicles are found that are not parked neatly. This study aims to obtain the existing capacity of parking locations at Depok Baru Station and to obtain parking characteristics (accumulation, duration of each vehicle, parking space turnover rate and parking index) of motorized vehicles in the Depok Baru Station area. This study uses quantitative methods, data collection is carried out by means of observation as primary data, including data on the number of incoming vehicles, data on the number of outgoing vehicles, data representing peak hours, peak days, normal hours, normal days, number of Parking Space Units (SRP) . The results of this study are that the existing parking lot obtained secondary data using the survey method to produce existing data on an area of 840m2 motorcycle parking area with a capacity of 300 SRP (parking space units) and a slope angle of 90° at Depok Baru Station. the largest accumulation stasis was 358 vehicles with an average parking duration of 12.20 hours on Tuesday 13 June 2023. During the eight days of the survey, the maximum parking volume was 480 vehicles with a maximum accumulated vehicle parking of 424 vehicles which occurred on Monday June 12, 2023, the highest turn over for motorcycle parking at Depok Baru Station reached 161.00%, therefore the performance of motorcycle parking is quite high. The capacity of motorcycle parking spaces at Depok Baru Station cannot accommodate the available parking space requirements. This can be reviewed by looking at the parking index which exceeds 100%.